CONCEPTUALIZING CORONA VIRUS METAPHOR IN MEDIA HEADLINES: A COGNITIVE SEMANTIC APPROACH - asnita sirait; Kristining Seva; Thomson Radesman Lingga (Universitas Widyatama, 2020)
This study aimed at investigating how media depict corona virus through the use of metaphors in the headines and conceptualizing the metaphor by the use of mappings. The data were gained from the headlines of two English online media in Indonesia, The Jakartapost and Kompas.id published from March to May, 2020. The data analyses applied qualitative descriptive study through the framework of the Conceptual Metaphor Theory (CMT) proposed by Lakoff and Johnson. The data were first selected from the headlines which were then analyzed and categorized to relevant conceptual metaphors through the bridge of mappings to understand and to characterize the relationship between two concepts (source and target domains) in the metaphorical process. The study found that the most used of conceptual metaphors of corona virus is CORONA VIRUS IS A WAR. Despite its controversial issue as to blow up people